Effects of physiotherapy in 28-year-old male with Bell’s palsy following vestibular schwannoma - Tayal, Akshita; Aggarwal, Nidhi; Siwach, Priyanka (International Journal of Research in Medical Sciences, 2023)
Schwannomas are benign, well-encapsulated, slow growing nerve sheath tumors. Vestibular schwannomas (VS) are one of the commonest intracranial tumors that arise from the Schwann cells at cerebropontine angle. Post-surgical complications are highly prevalent where Bell’s palsy is one of the most reported problems. Bell’s palsy is a lower motor neuron condition characterized by rapid and unilateral paresis of 7th cranial nerve. A 28-year-old male was diagnosed with vestibular schwannoma followed by Bell’s palsy. Patient presented with facial muscle paresis along with the Bell’s phenomenon. Neurological examination revealed 7th cranial nerve involvement (house Brackmann scale score-VI). Various physiotherapy interventions including facial PNF, facial exercise, electrical stimulation, biofeedback through mirror exercises, facial soft tissue manipulation and ultrasound therapy were used that reduced the house Brackmann scale score to I/VI.